Educational Needs for Coping with Clinical Uncertainty in Physiotherapy - Aday Infante Guedes; María del Pino Quintana Montesdeoca; María Del Pilar Etopa Bitata (Education Sciences, 2023)
The physiotherapist inevitably experiences clinical uncertainty, as they treat a wide variety of pathologies and, in some situations, will be the first professional contact. However, clinical uncertainty has yet to be sufficiently studied in physiotherapy and is not explicitly contemplated in physiotherapist training. This research aims to evaluate recent physiotherapy graduates’ tolerance to clinical uncertainty to determine their educational needs. A cross-sectional quantitative observational study was conducted in which the sample consisted of 31 recent graduates. They were given a self-developed questionnaire to assess “Tolerance to Uncertainty in Physiotherapy” (TUP). The results showed that the mean score obtained was 57.7 (6.49) points, with a minimum of 43 and a maximum of 69 points. The dimension “sources of uncertainty” scored the highest. The results revealed a profile of novice physiotherapists with a medium intolerance to uncertainty, nervous about unknown diagnoses. It is necessary to consider tolerance to uncertainty in the curricular programmes of physiotherapy degrees that can cover the needs described here.